1999
DOI: 10.1093/oxfordjournals.aje.a009817
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Peripheral Arterial Disease and Associated Risk Factors in American Indians: The Strong Heart Study

Abstract: Studies of peripheral arterial disease (PAD) in minority populations provide researchers with an opportunity to evaluate PAD risk factors and disease severity under different types of conditions. Examination 1 of the Strong Heart Study (1989-1992) provided data on the prevalence of PAD and its risk factors in a sample of American Indians. Participants (N = 4,549) represented 13 tribes located in three geographically diverse centers in the Dakotas, Oklahoma, and Arizona. Participants in this epidemiologic study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
1
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(89 citation statements)
references
References 0 publications
5
79
1
4
Order By: Relevance
“…In other words, a patient has a higher risk of all-cause and CVD mortality with a lower ABI. The adjusted risk of all-cause and CVD mortality for the 0.91-0.99 group, defined as the equivocal ABI level by PAD guidelines, 19 was not significantly different from the 1.00-1.40 group in this study.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…In other words, a patient has a higher risk of all-cause and CVD mortality with a lower ABI. The adjusted risk of all-cause and CVD mortality for the 0.91-0.99 group, defined as the equivocal ABI level by PAD guidelines, 19 was not significantly different from the 1.00-1.40 group in this study.…”
Section: Discussioncontrasting
confidence: 63%
“…18 This cutoff point has also been accepted by the Strong Heart Study (SHS) where the upper limit of normal ABI should not exceed 1.40. 19 More recently, the American College of Cardiology and the American Heart Association (ACC/AHA) guidelines have recommended ABI p0.90 as the criterion for the diagnosis of PAD. 20 Thus, our study adopted this recommendation for participants with an ABI p0.90 in either leg as low ABI.…”
Section: Diagnosis Of Padmentioning
confidence: 99%
“…24,25 This cutpoint has been related to prevalent and incident CVD and all-cause mortality in several studies 1,2,5,7,8 and has been used in other studies of American Indians 26 and in previous work in the SHS. 3 Participants who had an ABI Ͻ0.90 in either leg were categorized as having low ABI.…”
Section: Definition Of Abi Categoriesmentioning
confidence: 99%
“…[1][2][3] Prospective studies using the ankle brachial index (ABI) have shown that a low ABI predicts fatal and nonfatal CHD and all-cause mortality in people with and without existing clinical coronary artery disease and among people with existing peripheral vascular disease. 4 -10 Low ABI has been linked with incident stroke in the elderly.…”
mentioning
confidence: 99%
“…However, the role of albuminuria as a risk factor for PAD has been evaluated in mostly small studies. These studies suggest that albuminuria may be an important risk factor for PAD in the general population [10,11] and in high risk populations of diabetic subjects [12][13][14][15] or hypertensive subjects [16,17]. The hypothesis of this study was that albuminuria is associated positively with PAD in a racially diverse group of diabetic and nondiabetic subjects without a history of CVD.…”
Section: Introductionmentioning
confidence: 97%